2011
DOI: 10.1021/jf1042689
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical-Assisted Extraction and Antioxidant Activities of Kaempferol Glycosides from Camellia oleifera Abel. Meal

Abstract: A mechanochemical-assisted extraction (MCAE) method was proposed and investigated for the fast extraction of two kaempferol glycosides (kaempferol-3-O-[2-O-β-D-galactopyranosyl-6-O-α-L-rhamnopyranosyl]-β-D-glucopyranoside and kaempferol-3-O-[2-O-β-D-xylopyranosyl-6-O-α-L-rhamnopyranosyl]-β-D-glucopyranoside) from Camellia oleifera Abel. meal. The effects of operating parameters in terms of NaOH content, grinding time, extraction time, and ratio of solution to solid were evaluated by means of response surface m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 29 publications
(34 reference statements)
2
31
0
Order By: Relevance
“…DEPT-135 spectrum showed the presence of two methyls, one methylene, 21 methines, and nine nonprotonated carbons. By comparing the above data with the reported data (Fang, Rao, & Tzeng, 2005), compound 2 was determined to be kaempferol-3 (Chen, Wu et al, 2010;Liau et al, 2017;Zhu et al, 2011), the present study reported another two kaempferol glycosides isolated and purified by HSCCC from C. oleifera meal. It should be noted that O-glycosylation of these two compounds occurs at both C-3 and C-7 positions, which was seldom found in C. oleifera and other natural plants.…”
Section: Structural Identificationsupporting
confidence: 57%
See 2 more Smart Citations
“…DEPT-135 spectrum showed the presence of two methyls, one methylene, 21 methines, and nine nonprotonated carbons. By comparing the above data with the reported data (Fang, Rao, & Tzeng, 2005), compound 2 was determined to be kaempferol-3 (Chen, Wu et al, 2010;Liau et al, 2017;Zhu et al, 2011), the present study reported another two kaempferol glycosides isolated and purified by HSCCC from C. oleifera meal. It should be noted that O-glycosylation of these two compounds occurs at both C-3 and C-7 positions, which was seldom found in C. oleifera and other natural plants.…”
Section: Structural Identificationsupporting
confidence: 57%
“…Although several kaempferol glycosides have been previously identified from C . oleifera meal, such as kaempferol 3‐ O ‐[2‐ O ‐ β ‐D‐xylopyranosyl‐6‐ O ‐ α ‐L‐ rhamnopyranosyl]‐ β ‐D‐glucopyranoside and kaempferol 3‐ O ‐[2‐ O ‐ β ‐D‐ galactopyranosyl‐6‐ O ‐ α ‐L‐rhamnopyranosyl]‐ β ‐D‐glucopyrnoside (Chen, Wu et al., ; Liau et al., ; Zhu et al., ), the present study reported another two kaempferol glycosides isolated and purified by HSCCC from C. oleifera meal. It should be noted that O ‐glycosylation of these two compounds occurs at both C‐3 and C‐7 positions, which was seldom found in C. oleifera and other natural plants.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Response surface methodology (RSM) was used to build a model from four independent factors including extraction time, pressure, temperature and ethanol content of modifier. Zhu, Lin, Chen, Xie, and Wang (2011) used a mechanochemical-assisted extraction (MCAE) method in extracting kaempferol from Camellia oleifera Abel. meal.…”
Section: Extractionmentioning
confidence: 99%
“…Meanwhile, there are also various biological activities and active constituents in C. oleifera meal, which has drawn increasing attention and considerable interest during the past decades (Bin et al, 2010). Two kaempferol glycosides had been found in C. oleifera meal and showed an inhibitory effect on the arachidonate 5-lipoxygenase of RBL-1 cells (Sekine et al, 1991(Sekine et al, , 1993Li et al, 2010;Zhu et al, 2011). Furthermore, tea saponin (TS) is a polysaccharide terpenoid in the meal and confers it many pharmacological activities, such as anti-inflammatory (Chattopadhyay et al, 2004;Yuan et al, 2006), antiallergic (Akagi et al, 1997), anticholesterol (Feng et al, 1998) and hepatoprotective effect (Lai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%